Pharmacogenomics of soft tissue sarcomas: New horizons to understand efficacy and toxicity. (2022) - Gambale, Elisabetta; Boddi, Anna; Pasqui, Adriano; Campanacci, Domenico Andrea; Scoccianti, Guido; Palchetti, Ilaria; Bernini, Andrea; Antonuzzo, Lorenzo; Pillozzi, Serena
Highlights: Clinical response to therapies is limited to a small subset of soft tissue sarcoma (STS) patients. Genetic polymorphisms may influence drug response and toxicities. Pharmacogenomic markers are located in drug metabolizing enzymes and transporters. Single-nucleotide polymorphisms are suitable biomarkers for toxicity and drug response. Abstract: Clinical responses to anticancer therapies in advanced soft tissue sarcoma (STS) are unfortunately limited to a small subset of patients. Much of the inter-individual variability in treatment efficacy and risk of toxicities is as result of polymorphisms in genes encoding proteins involved in drug pharmacokinetics and pharmacodynamics. Therefore, the detection of pharmacogenomics (PGx) biomarkers that might predict drug response and toxicity can be useful to explain the genetic basis for the differences in treatment efficacy and toxicity among STS patients. PGx markers are frequently located in transporters, drug-metabolizing enzyme genes, drug targets, or HLA alleles. Along this line, genetic variability harbouring in the germline genome of the patients can influence systemic pharmacokinetics and pharmacodynamics of the treatments, acting as predictive biomarkers for drug-induced toxicity and treatment efficacy. By linking drug activity to the functional complexity of cancer genomes, also systematic pharmacogenomic profiling in cancer cell lines and primary STS samples represents area of active investigation that could eventually lead to enhanced efficacy and offer a powerful biomarker discovery platform to optimize current treatments and improve the knowledge about the individual's drug response in STS patients into the clinical practice. Graphical abstract: Image, graphical abstract